METHODS OF TEACHING READING IN THE ARABIC LANGUAGE - Amal Sabah Rdam Al Tai (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to know the methods of teaching reading in the Arabic language. This study was conducted in Iraq. The researcher seeks to gather in various reading matters in terms of the most important methods used in the reading lesson, the concept of reading, the most important types of reading, the methods of teaching, and methods of analyzing them. The researcher followed the descriptive approach in conducting the current study and sought to collect what has to do with the subject of the study with his theoretical side.